Feminist thought : a more comprehensive introduction - Tong, Rosemarie Putnam (Westview, 1998)
In this second edition of her 1989 survey on feminist theory, Rosemarie Tong provides a more comprehensive and substantially redrawn map of twentieth-century feminist thinking. Besides providing up-to-date coverage of liberal, radical (libertarian and cultural), and Marxist-socialist schools of feminism, she covers psychoanalytic, existentialist, and postmodern feminism. All the chapters have been rethought and new chapters on ecofeminism and multicultural and global feminism have been added. }In this second edition of her 1989 survey on feminist theory, Rosemarie Tong provides a more comprehensive and substantially redrawn map of twentieth-century feminist thinking. Besides providing up-to-date coverage of liberal, radical (libertarian and cultural), and Marxist-socialist schools of feminism, she covers psychoanalytic, existentialist, and postmodern feminism. All the chapters have been rethought and new chapters on ecofeminism and multicultural and global feminism have been added. In the clear-sighted and accessible style for which has become known, Tong guides the reader through the complexities of even the most notoriously difficult thinkers. Students will become familiar with many of the essential figures in the feminist tradition as well as some of the issues that have been of special concern to women (e.g., pornography, reproductive technology, housework, the environment, and militarism). Moreover, students are repeatedly urged to consider the many differences that separate women (class, race, ethnicity, age, nationality, religion) as well as the sameness that continue to unite women.Tong treats all views with respect and encourages the reader to think both sympathetically and critically about what feminism is and what relevance it has to their own lives. As valuable as the first edition of Feminist Thought, this second edition surpasses its predecessor in depth and breadth. Clearly, Tong believes that feminist thought is still developing even as it approaches the millennium. }